Efficiency of Arachis hypogaea Ash in Aniline Adsorption from Aqueous Solution: A Thermodynamic and Kinetic Study - somayeh rahdar; somayeh; shahin Ahmadi (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: Aniline is a simple aromatic compound that has a wide application in various industries. This compound has mutagenic and carcinogenic properties. Given the solubility and high toxicity of aniline, the entrance of this compound into the surface and ground water can endanger human and environment and disturb aqueous species life . Regarding this, the present study was conducted to investigate the elimination of aniline from aqueous solutions by means of Arachis hypogaea ash.Methods: The equilibrium adsorption level was determined as a function of the solution pH (i.e., 3, 5, 7, 9, and 11), contact time (i.e., 20-150 min), adsorbent doses (i.e., 0.4, 0.6, 0.8, 1, 1.2, and 1.5 g/L), and aniline initial concentration (i.e., 20-150 mg/L). Adsorption kinetic was assessed using pseudo first order, pseudo second order, and Elovich kinetics.Results: According to the results, Arachis hypogaea ash was capable of reducing aniline by 65% at the pH of 7, initial aniline concentration of 90 mg/ L, contact time of 120 min, and dosage of 0.8 g/L. Regarding the adsorption kinetics, and a second-order equation resulted in the achievement of the best fit. Conclusion: As the finding indicated, Arachis hypogaea ash as an inexpensive absorbent was a quite effective substance for the removal of aniline from water and wastewater.